Analisis Nilai Religius Tokoh Utama Film Animasi Upin Dan Ipin Geng Pengembaraan Bermula - Dian Nor Apifah; Alifiah Nurachmana; Yuliati Eka Asi; Rustiana Ummy; Winda Saptaniarsih (Universitas Palangka Raya, 2022)
This study aims to find religious values in the main characters of the animated film Upin and Ipin in the form of: (1) Honesty (2) Justice (3) Benefit for others (4) Humility (5) Work efficiently (6) Future vision ( 7) High discipline (8) Balance. Research uses a descriptive approach. The source of the research data is the animated film Upin and Ipin The Beginning Gang of Adventures. Data obtained by non-participant observation. The data analysis techniques used are (1) Data Collection (2) Data Reduction (3) Data Presentation (4) Drawing Conclusions or Verification. The validity of the data obtained by triangulation. The results of this study are (1) The form of religious values in the form of honesty is found in all the main characters. (2) Forms of religious values in the form of justice are found in the characters Badrol, Lim, Ros, and Rajoo (3) Forms of religious values in the form of benefiting others are found in all the main characters (4) Forms of religious values in the form of humility are found in all the main character (5) The form of religious values that manifests efficient work is found in all the main characters (6) The form of religious values that is in the form of future vision is present in all the main characters (7) The form of religious values that is in the form of high discipline is found in all the main characters (8) The form of religious values in the form of balance is found in all the main characters.